Experimental heatwaves facilitate invasion and alter species interactions and composition in a tropical host‐parasitoid community - Chen, J; Lewis, O (Wiley, 2023)
As mean temperatures increase and heatwaves become more frequent, species are expanding their distributions to colonise new habitats. The resulting novel species interactions will simultaneously shape the temperature-driven reorganization of resident communities. The interactive effects of climate change and climate change-facilitated invasion have rarely been studied in multi-trophic communities, and are likely to differ depending on the nature of the climatic driver (i.e., climate extremes or constant warming). We re-created under laboratory conditions a host-parasitoid community typical of high-elevation rainforest sites in Queensland, Australia, comprising four Drosophila species and two associated parasitoid species. We subjected these communities to an equivalent increase in average temperature in the form of periodic heatwaves or constant warming, in combination with an invasion treatment involving a novel host species from lower-elevation habitats. The two parasitoid species were sensitive to both warming and heatwaves, while the demographic responses of Drosophila species were highly idiosyncratic, reflecting the combined effects of thermal tolerance, parasitism, competition, and facilitation. After multiple generations, our heatwave treatment promoted the establishment of low-elevation species in upland communities. Invasion of the low-elevation species correlated negatively with the abundance of one of the parasitoid species, leading to cascading effects on its hosts and their competitors. Our study, therefore, reveals differing, sometimes contrasting, impacts of extreme temperatures and constant warming on community composition. It also highlights how the scale and direction of climate impacts could be further modified by invading species within a bi-trophic community network.